Simultaneous Application of Pressure‐Infusion‐Gyration to Generate Polymeric Nanofibers. Issue 6 (27th March 2017) - Hong, Xianze; Mahalingam, Suntharavathanan; Edirisinghe, Mohan
Abstract : A new polymer nanofiber manufacturing process which allows attainment of desired fibre characteristics using the combined effect of variables feed composition, flow, pressure and rotation is uncovered. The features of the process are illustrated using several systematic optimisation experiments and high speed camera videos on fiber generation. Abstract : Polymeric nanofibers are a fascinating class of material that has been widely used in a myriad of applications, including fiber reinforced composites, protective clothing, and chemical sensors. Here, the science of the combined application of external pressure, controlled infusion of polymer solution and gyration, which allows mass production of uniform polymeric nanofibers in a single step, is uncovered. Using poly(ethylene oxide) as an example this study shows the use of this novel method to fabricate polymeric nanofibers and nanofibrous mats under different combinations of processing parameters such as working pressure (1 × 10 5 to 3 × 10 5 Pa), rotational speed (10 000–36 000 rpm), infusion rate (500–5000 µL min −1 ), and fiber collection distance (4–15 cm). The morphologies of the nanofibers are characterized using scanning electron microscopy and anisotropy of alignment of fiber is studied using 2D fast Fourier transform analysis. A correlation between the product morphology and the processing parameters is established. The produced fibers are in a range of 50–850 nm at an orifice‐to‐collector distance of 10 cm. The results indicate that the pressure coupled infusion gyration (PCIG) offers a facile way for forming nanofibers and nanofiber assemblies.